Geld und Gott, Geld oder Gott?: Neue Impulse für die theologische Rede über Geld - Trugenberger, Julius (Evangelische Theologie, 2023)
Although money is of great importance for modern society, it has not been a prominent topic in Protestant theology. The aim of this article is to give new impetus to the theological discourse on money. Niklas Luhmann and Georg Simmel are two important thinkers who have dealt intensively with the role of money in modernity. For Luhmann, money is an important factor of social differentiation, and according to Simmel, it interferes with God and faith in many ways. The paper argues that if theologians take the insights of these two authors into account, they will better understand the modern world shaped by money. At the same time, their reflection on money and their discourse about it will become more differentiated and more nuanced.